2018
DOI: 10.1029/2018jb015567
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Deformation Process in the Mid‐Niigata Region of the Niigata‐Kobe Tectonic Zone as Observed by Dense GPS Network Before, During, and After the Tohoku‐Oki Earthquake

Abstract: We evaluate response of Mid‐Niigata during the preseismic, coseismic, and postseismic periods of the 2011 Mw9.0 Tohoku‐oki earthquake by analyzing strain distributions based on a dense Global Positioning System network. Decomposition of the coseismic E‐W strain according to its wavelength shows localized elastic extension, while persistent localized contraction in the short‐wavelength component within a narrow zone of 40‐ to 60‐km width is significant before and after the event, implying the persistence of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…According to the analysis of GNSS data by Meneses-Gutierrez et al (2018), the zone with about 10-20% smaller elastic stiffness spanning the width of 30-40 km is needed in order to explain coseismic deformation data. Because the width of the NKTZ is taken to be about 100 km in this study, this effect corresponds to about 5% exaggeration of the elastic deformation in average within the NKTZ than the surrounding area.…”
Section: Abbreviationsmentioning
confidence: 99%
“…According to the analysis of GNSS data by Meneses-Gutierrez et al (2018), the zone with about 10-20% smaller elastic stiffness spanning the width of 30-40 km is needed in order to explain coseismic deformation data. Because the width of the NKTZ is taken to be about 100 km in this study, this effect corresponds to about 5% exaggeration of the elastic deformation in average within the NKTZ than the surrounding area.…”
Section: Abbreviationsmentioning
confidence: 99%
“…We support this interpretation. Besides, the central Japan region includes the Niigata-Kobe Tectonic Zone with active inland earthquakes and high strain rates (Sagiya et al 2000;Meneses-Gutierrez et al 2018). The small azimuthal difference between τ Hmax and S Hmax may be related to the inelastic deformation of the lower crust or mantle beneath the Niigata-Kobe Tectonic Zone (Iio et al 2002;Yamasaki and Seno 2005) serving to bridge the azimuthal difference.…”
Section: Temporal Change Of Azimuthal Differencementioning
confidence: 99%
“…On the whole, the differences in the azimuths of the maximum contraction of geodetic strain rate (τ Hmax ) and those of the maximum compressive stress (S Hmax ) well corresponded to regional seismotectonics for the Japanese Islands, regardless of speci c areas such as a forearc. While they probably re ected the past deformation history in each region, they may also be related to the spatially heterogeneous inelastic rheology of rocks (e.g., Meneses-Gutierrez et al 2018;Becker et al 2018;Yuasa et al 2020). Further interesting results on those details can be obtained by estimating offshore strain-rate elds based on sea oor crustal deformation data (e.g., Yokota et al 2018).…”
Section: Temporal Change Of Azimuthal Differencementioning
confidence: 99%
“…As mentioned above, Meneses-Gutierrez and Sagiya (2016) have successfully separated inelastic deformation from observed GNSS data around the Niigata plain in the northern NKTZ. Following the study, to quantitatively explain the observed GNSS data, Meneses-Gutierrez et al (2018) have constructed a model that has an aseismic fault embedded in an elastically heterogeneous medium. Because the study also mainly focused on the separation of the elastic and inelastic deformation, it paid relatively less attention on the difference of inelastic strain rates before and after the Tohoku-oki earthquake.…”
Section: Crustal Deformation In the Nktzmentioning
confidence: 99%
“…However, when we examine the observed GNSS data in detail, we can notice that the separated inelastic strain rate is significantly faster before the Tohoku-oki earthquake. Meneses-Gutierrez et al (2018) tried to interpret this observation with a combination of persistent inelastic deformation and elastic heterogeneity effect. However, a possibility of significant temporal change of inelastic deformation has not been seriously considered.…”
Section: Crustal Deformation In the Nktzmentioning
confidence: 99%